2010
DOI: 10.1038/nnano.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

Biologically templated photocatalytic nanostructures for sustained light-driven water oxidation

Abstract: Over several billion years, cyanobacteria and plants have evolved highly organized photosynthetic systems to shuttle both electronic and chemical species for the efficient oxidation of water. In a similar manner to reaction centres in natural photosystems, molecular and metal oxide catalysts have been used to photochemically oxidize water. However, the various approaches involving the molecular design of ligands, surface modification and immobilization still have limitations in terms of catalytic efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(166 citation statements)
references
References 30 publications
1
165
0
Order By: Relevance
“…This simple peptide design that affords a complex material will allow us to explore the ability to tune the material through variations in peptide sequence, porphyrin selection, porphyrin position and added redox hopping sites to tune the electron transfer pathway rate and efficiency. The observed charge separation will also allow us to explore the assembly as the fundamental construct of DSCs 5,6 and photocatalytic watersplitting systems 48,49 .…”
Section: Discussionmentioning
confidence: 97%
“…This simple peptide design that affords a complex material will allow us to explore the ability to tune the material through variations in peptide sequence, porphyrin selection, porphyrin position and added redox hopping sites to tune the electron transfer pathway rate and efficiency. The observed charge separation will also allow us to explore the assembly as the fundamental construct of DSCs 5,6 and photocatalytic watersplitting systems 48,49 .…”
Section: Discussionmentioning
confidence: 97%
“…[70] It was found that the system consisting in In an attempt to mimic this type of natural light harvesting centers, the capsid of the M13 virus has been used as platform to attach in an ordered manner porphyrin molecules at an appropriate distance on a linear configuration (Scheme 16). [71,72] Apparently, the protein of the M13 virus contains in a regular and periodic way lysine amino acids that are able to bind strongly to the porphyrin through their free primary amino groups.…”
Section: Photobiocatalysts Mimicking Psiimentioning
confidence: 99%
“…Recently, Nam and co-workers imtroduced a biologically templated nanostructure for visible light driven water oxidation that uses a genetically engineered virus scaffold to mediate the co-assembly of zinc porphyrins (photosensitizer) and iridium oxide clusters (water oxidizing catalyst) (Nam et al, 2010). Their results suggested that the biotemplated nanoscale assembly of functional components is a promising route to improved photocatalytic water-splitting systems.…”
Section: Genetic Engineering Modelsmentioning
confidence: 99%